PENGEMBANGAN MODUL LOGIKA MATEMATIKA BERBASIS HIGHER ORDER THINGKING SKILLS UNTUK MENINGKATKAN KEMANDIRIAN BELAJAR SISWA - Ayu Wulandari; Rosliana Siregar; Syahlan Syahlan (MES: Journal of Mathematics Education and Science, 2022)
This study aims to develop teaching materials in the form of mathematics modules based on Higher Order Thinking Skills to increase student learning independence at SMK YPK Medan. The mathematical logic module developed is feasible to use and has met the valid, practical and effective criteria. The method used in this study is a Research and Development method with define, design, develop, disseminate. The results of the research that have been carried out show that the module developed is valid. This is based on the results of four different validators in terms of material, language, and design with an average score of 4.0 and are in the valid category. Practicality is obtained from the results of student questionnaires with an average score of 58.47 and is in the practical category. The effectiveness is obtained from the results of increasing student learning independence on the first trial test of 68.3 and on the second trial test of 81.65 which is included in the effective improvement category.